2022
DOI: 10.1021/acs.inorgchem.1c03432
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Luminescence Thermometer with Field-Induced Slow Magnetic Relaxation Based on a Heterometallic Cyanido-Bridged 3d–4f Complex

Abstract: The 1:1:1 reaction of DyCl 3 •6H 2 O, K 3 [Co(CN) 6 ] and bpyO 2 in H 2 O has provided access to a complex with formula [DyCo-(CN) 2) was also precipitated (also in a high yield) using K 3 [Fe(CN) 6 ] instead of K 3 [Co(CN) 6 ]. Their structures have been determined by single-crystal X-ray crystallography and characterized based on elemental analyses and IR spectra. Combined direct current (dc) and alternating current (ac) magnetic susceptibility revealed slow magnetic relaxation upon application of a dc fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…It is worth mentioning that there are few examples of Dy III -based SMM optical thermometers in the literature, and most of these examples based their luminescent thermometric features on solely Dy III emissions. 7 b ,11,12,15,17 Our system accesses the thermometric characteristics involving the ligand ascribed to the triplet emission in combination with Dy III emission and, to the best of our knowledge, there is only one example in the literature that shares this feature. 7 b As can be seen in Table 1, this related compound is a dinuclear dysprosium complex, and, although the number of homodi- or polynuclear dysprosium SMMs is very low, the data may suggest that this phenomenon is more favoured in SMMs with more than one Dy III ion than in SIMs of the same metal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that there are few examples of Dy III -based SMM optical thermometers in the literature, and most of these examples based their luminescent thermometric features on solely Dy III emissions. 7 b ,11,12,15,17 Our system accesses the thermometric characteristics involving the ligand ascribed to the triplet emission in combination with Dy III emission and, to the best of our knowledge, there is only one example in the literature that shares this feature. 7 b As can be seen in Table 1, this related compound is a dinuclear dysprosium complex, and, although the number of homodi- or polynuclear dysprosium SMMs is very low, the data may suggest that this phenomenon is more favoured in SMMs with more than one Dy III ion than in SIMs of the same metal.…”
Section: Resultsmentioning
confidence: 99%
“…One way to overcome this impasse is to build microdevices with materials capable of also acting as in situ thermometers. In this sense, there are some very recent publications that try to provide solutions for the measurement of temperature in molecular magnets, making use of luminescent thermometry, [7][8][9][10][11][12][13][14][15][16][17] and some of the achievements were summarised by Murugesu and colaborators. 18 Among these works, most studies have been carried out with homodinuclear compounds of Dy III , 7b Tb III , 7c or Yb III .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to succeed in this, we used the red-emissive octahedral diamagnetic [(CoCN) 6 ] 3− linker as an alternative source for effective energy transfer to 4f-metal ions. Following this strategy we have recently reported a new multifunctional hetero-dinuclear compound [DyCo III (CN) 6 (bpyO 2 ) 2 (H 2 O) 3 ]·4H 2 O, 43 exhibiting both SMM magnetic properties and temperature-dependent photoluminescent characteristics. High resolution optical studies revealed a maximum thermal sensitivity of 1.84% K −1 at 70 K, which is higher than the acceptable sensitivity boundary of 1% K −1 for high performance luminescence thermometers in a broad range of temperatures between 40–140 K. Magnetic studies showed slow relaxation upon application of a DC field.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution optical studies revealed a maximum thermal sensitivity of 1.84% K −1 at 70 K, which is higher than the acceptable sensitivity boundary of 1% K −1 for high performance luminescence thermometers in a broad range of temperatures between 40–140 K. Magnetic studies showed slow relaxation upon application of a DC field. Replacing the Co III metal ion with the Fe III ion, we managed to isolate the isomorphous antiferromagnetic coupled Dy–Fe pair, [DyFe III (CN) 6 (bpyO 2 ) 2 (H 2 O) 3 ]·4H 2 O 43 featuring SMM properties but unfortunately its emission is governed by the bpyO 2 ligand due to the quenching of the external carriers in the Fe III ion. Finally, two isomorphous and structurally characterised heterodimers have been reported, of the type [LnFe III (CN) 6 (bpyO 2 ) 2 (H 2 O) 3 ] where (Ln = Sm, Gd).…”
Section: Introductionmentioning
confidence: 99%